Key success driver of Japanese elite sport system: Elite athletes' and elite coaches` perspective - Funahashi, H.; Nagamatsu, J.; Shirai, K.; Yamashita, S.; Nakamura, H.; Yamada, E.; Waku, T.; Mano, Y. (Sport Science Research, 2012)
The purpose of this research was to examine policy-related success drivers of the Japanese elite sport system by conducting an evaluation of the elite sport climate with Japanese elite athletes (n=105) and coaches (n=62) as the survey subjects. The sub-analysis investigated which specific policy-related factors describe the difference between medallist (n=43) and non-medallist (n=62). The study was drawn from the research framework and scoring system developed by De Bosscher et al. (2006, 2008, 2009, 2010) that is built on the SPLISS (Sports Policy Factors leading to International Sporting Success) model. The result showed that the elite sport climate was very well maintained for the evaluation items of `training facilities`, and this item could be considered to be policy-related success drivers in the Japanese elite sport system. In addition to this, the elite sport climate was not adequately maintained in terms of `post career support`, and this item could be regarded as an underdeveloped area in Japanese elite sport system policies. The sub-analysis revealed that there was no significant difference between medal winning and non medal winning athletes in the overall evaluation of elite sport climate, which suggested that the elite sport climate for medal-winning and non-medal-winning elite athletes are maintained to the same standard.